Pelatihan Pengolahan Ikan Oreochromis niloticus Dan Pangaside Menjadi Cemilan Sehat Dan Bergizi Dalam Upaya Pengentasan Stunting di Kampung Sawit Permai - Ferdian Yudha Pratama; Irda Sayuti; Lucky Manuel Sihotang; Mutia Adlina Rifani; Putri Dini Dameria; Elisabeth Elisabeth; Kayla Annasya Varandra; Gustri Musdalifah; Sara Gleri Lubis; Mariamlie Mariamlie; Arie Ferdinandsyah (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
The number of stunting in Sawit Permai Village is the highest level in Dayun Subdistrict and is a serious problem in the growth of children in the area. The research methodology involves a series of activities, including educational outreach, posyandu (Integrated Healthcare Center) support and most importantly the training of processing Nile Tilapia (Oreochromis Niloticus) and Catfish (Pangasiidae) into healthy foods. This training aims to increase people's knowledge and skills in using Catfish and Nile Tilapia as source of healthy and nutritious protein. The research results show that through this training, the people of Kampung Sawit Permai can produce healthy snacks that are rich in nutrients from fish. This is expected to contribute significantly to improving children's nutrition and reducing stunting rates in this region. This research makes an important contribution to prevent stunting in Kampung Sawit Permai and can be used as an example for other regions in utilizing local resources to improve children's health.